Realistic Mathematics Education as a Contextual Approach in Overcoming Learning Difficulties Circle - Pujilestari, Pujilestari; Juliangkary, Eliska (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study explores the application of the Realistic Mathematics Education (RME) model as a contextual approach to overcome learning difficulties among eighth-grade students in understanding the topic of circles. The research was conducted through a Classroom Action Research (CAR) method in two cycles at SMPN SATAP 1 Pringgabaya, involving 13 students as subjects. The implementation of RME focused on bridging abstract mathematical concepts with real-life experiences through contextualized problem-solving, group activities, and visual representations. Data were collected through tests, questionnaires, and classroom observations. The results showed a notable improvement in students’ conceptual understanding, with the average score increasing from 62.91 in cycle I to 72.5 in cycle II, and classical completeness rising from 58.33% to 75%. Furthermore, learning interest increased from 61.42% to 79.45%. These findings indicate that RME not only enhances students' cognitive outcomes but also positively influences their engagement and motivation. Thus, RME serves as an effective pedagogical strategy for teaching geometry, particularly in visualizing and contextualizing mathematical concepts such as circles.